(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Salacia reticulata is an important medicinal plant, that is widely distributed in some parts of the sub-continent of India. Salacinol, a biologically active component found in the plant, has been shown through numerous pharmaceutical studies to have anticancer potential. Apoptosis exerts a significant influence on the regulation of cellular processes. A crucial phenomenon in biological systems is the induction of apoptosis by endogenous and exogenous stimuli like UV rays, oxidative stress, and genotoxic chemicals. DNA damage regulates other proteins that activate intrinsic and extrinsic apoptotic pathways, stabilizes p53 in the nucleus and cytoplasm Apoptotic pathway dysfunction may result in conditions like autoimmune disorders, neurodegenerative disorders, and cancer. Recently, powerful apoptosis-inducing substances connected to human health were discovered to inhibit the promotion, growth, and occurrence of tumors as well as cellular inflammatory reactions. Apoptosis-inducing medications are used in therapy to treat both cancerous and non-cancerous cells. A group of structurally and functionally related proteins known as the Inhibitors of Apoptosis (IAP) act as endogenous inhibitors of programmed cell death. In this current study, salacinol was analyzed and subjected to pharmacokinetics screening. An attempt was made to study the interaction between three IAP proteins (BIRC5-3UIH, 3UII, 3UIK) with salacinol using Auto dock software. Salacinol was found to have the best interaction with the IAP target protein.